192k views
3 votes
Given that f(x) = x^2 - 8x + 12 and g(x) = -6, find (f/g)(x) and express the result in standard form

User Eltariel
by
5.6k points

1 Answer

0 votes

We are given the following two functions


\begin{gathered} f(x)=x^2-8x+12 \\ g(x)=-6_{} \end{gathered}

We are to find (f/g)(x)

(f/g)(x) is basically the division of function f(x) by function g(x)


((f)/(g))(x)=(f(x))/(g(x))=(x^2-8x+12)/(-6)=(x^2)/(-6)-(8x)/(-6)+(12)/(-6)=-(1)/(6)x^2+(2)/(3)x-2

Therefore, the function (f/g)(x) is


((f)/(g))(x)=-(1)/(6)x^2+(2)/(3)x-2

User NinjaKC
by
6.4k points